What Can the Prophet Muhammad Teach Us about Pandemics? - BinTaleb, Abdulaziz (Journal of religious and theological information, 2022)
This paper presents a review of the Prophet Muhammad’s traditions and teachings on pandemics. Relevant hadiths (the Prophet’s sayings) were identified through a systematic search based on the two authentic sources of Sunnah (prophetic traditions): Sahih al-Bukhari and Sahih Muslim. Of the 1,087 hadiths identified, 11 were included in this review. They were thematically analyzed, yielding five main themes: faith and pandemics; balancing faith with reason; the practice of cleanliness; isolating from others or quarantining; and patience, perseverance and optimism. The study found that the Prophet’s teachings regarding pandemics are full of wisdom and they have similarities with modern health advices and recommendations. In addition, the study suggests that learning about these traditions, is an introductory and creative way of learning about Islam and will help narrowing the information gap that separates the West and Islam.